Convergent-diffuser for small horizontal wind turbines - Ribeiro, Luís Frölén (2013)
A small horizontal axis wind turbine (HAWT) equipped with an annular Convergent-Diffuser (C-D) is under development. Small to medium wind turbines equipped solely with a diffuser are becoming quite common: the annular structure around the rotor decreases the pressure downstream the rotor, augmenting the air velocity and power output. It also may replace the wind vane. Previous studies for such designs, for instance Ohya, Y. 2010, report a maximum increase in power output up to 150%. We present the preliminary results of an alternative design for a convergent-divergent annular structure that involves the rotor. This structure was optimized in CFD-simulations and 2 models where built for wind tunnel measurements. The maximum power output obtained was 187% higher than the case for a rotor without the C-D structure. Field tests are undergoing at this moment for a C-D adapted in model Rutland 913 Windcharger of 90 W.